2020
DOI: 10.3390/nano11010022
|View full text |Cite
|
Sign up to set email alerts
|

Bone Regeneration Capacity of Newly Developed Uncalcined/Unsintered Hydroxyapatite and Poly-l-lactide-co-glycolide Sheet in Maxillofacial Surgery: An In Vivo Study

Abstract: Uncalcined/unsintered hydroxyapatite and poly-l-lactide-co-glycolide (u-HA/PLLA/PGA) is a new bioresorbable nanomaterial with superior characteristics compared with current bioresorbable materials, including appropriate mechanical properties, outstanding bioactive/osteoconductive features, and remarkably shorter resorption time. Nevertheless, the bone regeneration characteristics of this nanomaterial have not been evaluated in maxillofacial reconstructive surgery. In this study, we used a rat mandible model to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…However, the amount of newly formed regenerative bone in the u-HA/PLLA/PGA subgroup was almost equal to or greater than that in the u-HA/PLLA subgroup, although the difference was not statistically significant (Figure 6). This phenomenon was also observed in a previous study comparing u-HA/PLLA and u-HA/PLLA/PGA in a mandibular defect model [19]. In the present study, we compared OCN expression between two materials by IHC staining.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…However, the amount of newly formed regenerative bone in the u-HA/PLLA/PGA subgroup was almost equal to or greater than that in the u-HA/PLLA subgroup, although the difference was not statistically significant (Figure 6). This phenomenon was also observed in a previous study comparing u-HA/PLLA and u-HA/PLLA/PGA in a mandibular defect model [19]. In the present study, we compared OCN expression between two materials by IHC staining.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, the presence of u-HA particles in the new composite implies that u-HA/PLLA/PGA devices will also show similar bioactive osteoconductivity. The results of our previous study showed that u-HA/PLLA/PGA and u-HA/PLLA had comparable osteoconductive abilities in a rat mandibular defect model [ 19 ], confirming the potential applicability of this material to the maxillofacial region. According to immunohistochemical (IHC) analysis of Runx2 and LepR expression, bone marrow is the main source of osteoblastic cells [ 19 ].…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations